Associations between subjective social status and physical and mental health functioning among patients with hypertension. (November 2016) - Cené, Crystal W; Halladay, Jacqueline R; Gizlice, Ziya; Roedersheimer, Kyle; Hinderliter, Alan; Cummings, Doyle M; Donahue, Katrina E; Perrin, Andrew J; DeWalt, Darren A
We examine the cross-sectional association between subjective social status and self-rated physical and mental health functioning in 518 Black and White patients enrolled in a community-based hypertension control research study. We found that (1) subjective social status, measured using both a proximal and distal referent group, was positively associated with physical and mental health functioning scores independent of educational level, household income, or both; (2) the effect of subjective social status on physical and mental health functioning differed significantly by race when using the distal, not the proximal, referent group. When the associations differed, they were stronger for Whites than Blacks.